Association between Blood Mercury and Seafood Consumption in Korean Adults: KoNEHS Cycle 4 (2018~2020) - Ji-Eun Oh; Tae-Hyeong Kim; Eun-Hee Lee (Journal of experimental & biomedical sciences, 2024)
Mercury is a chemical pollutant widely present in the environment. Humans are generally exposed to mercury in the form of organic Hg (methylmercury) through the consumption of seafood. Koreans enjoy eating fish therefore blood mercury concentration is usually higher than in developed countries. By investigating blood mercury concentration according to the frequency of seafood consumption and sociodemographic factors, we aimed to identify recent trends in blood mercury concentration in Korean adults. This study was conducted using KoNEHS cycle 4 (2018~2020) from the National Institute Environmental Research Survey. The geometric mean concentration of blood mercury of the subjects was 2.959 (±1.018) ㎍/L, which was significantly higher in men than in women. It was observed that as the frequency of fish and shellfish consumption increased, the blood mercury concentration increased. In adjusted logistic regression, fish consumption was associated with 36.7% increased risk of blood mercury levels [Odds ratio, 1.367; 95% confidence interval (CI), 1.246~1.500], and shellfish consumption was associated with 26.5% increased risk of blood mercury levels [Odds ratio, 1.265; 95% confidence interval (CI), 1.134~1.410]. Blood mercury concentration was also found to increase as the socioeconomic level increased. In conclusion, the geometric mean concentration of blood mercury was increased compared to the one in the 3rd KoNEHS (2015~2017) and seafood consumption and socioeconomic level were still significantly associated with increasing blood mercury concentration in Korea. Therefore, it is necessary to encourage healthy seafood consumption habits and conduct continuous monitoring considering various factors to reduce blood mercury levels.